2000
DOI: 10.1212/wnl.54.11.2089
|View full text |Cite
|
Sign up to set email alerts
|

Do transient ischemic attacks have a neuroprotective effect?

Abstract: This study suggests that ischemic tolerance may play a role in patients with ipsilateral TIAs before CI, allowing better recovery from a subsequent ischemic stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
198
2
5

Year Published

2001
2001
2012
2012

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 262 publications
(220 citation statements)
references
References 27 publications
15
198
2
5
Order By: Relevance
“…Indeed, Kitagawa et al (1990) found that gerbils subjected to sublethal transient global ischemia exhibited reduced hippocampal CA1 neuronal death after a more severe ischemic insult 24 -48 hr later, and similar findings have been reported by others (for review, see Barone et al, 1998;Kirino, 2002). Ischemic tolerance also has been demonstrated in human clinical practice, because less severe strokes have been described in patients with prior ipsilateral transient ischemic attacks within a short period of time (Weih et al, 1999;Moncayo et al, 2000;Castillo et al, 2003). The remarkable protection induced by IPC makes this an attractive target for potential therapeutic development.…”
Section: Introductionsupporting
confidence: 59%
“…Indeed, Kitagawa et al (1990) found that gerbils subjected to sublethal transient global ischemia exhibited reduced hippocampal CA1 neuronal death after a more severe ischemic insult 24 -48 hr later, and similar findings have been reported by others (for review, see Barone et al, 1998;Kirino, 2002). Ischemic tolerance also has been demonstrated in human clinical practice, because less severe strokes have been described in patients with prior ipsilateral transient ischemic attacks within a short period of time (Weih et al, 1999;Moncayo et al, 2000;Castillo et al, 2003). The remarkable protection induced by IPC makes this an attractive target for potential therapeutic development.…”
Section: Introductionsupporting
confidence: 59%
“…This phenomenon has been described in several organs, especially the heart and brain. Ischemic tolerance has also been shown in human clinical practice; indeed, less severe strokes have been described in patients with prior ipsilateral transient ischemic attacks (TIA) within a short period of time (Weih et al, 1999;Moncayo et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…A recent human study showed that patients with repeated attacks of cerebral ischemia had a better neurologic outcome than patients without a previous ischemic attack (Moncayo et al, 2000). Another human study revealed that adenosine plasma levels were markedly increased and that the adenosine surge lasts days after transient ischemic attack and weeks after stroke (Pasini et al, 2000).…”
mentioning
confidence: 99%